2008
DOI: 10.1021/ja7102907
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Perspective on the Hydrogen Atom Transfer and Proton-Coupled Electron Transfer Mechanisms in Terms of Topographic Features of the Ground and Excited Potential Energy Surfaces As Exemplified by the Reaction between Phenol and Radicals

Abstract: The relation between the hydrogen atom transfer (HAT) and proton-coupled electron transfer (PCET) mechanisms is discussed and is illustrated by multiconfigurational electronic structure calculations on the ArOH + R(*) --> ArO(*) + RH reactions. The key topographic features of the Born-Oppenheimer potential energy surfaces that determine the predominant reaction mechanism are the conical intersection seam of the two lowest states and reaction saddle points located on the shoulders of this seam. The saddle point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
145
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(150 citation statements)
references
References 107 publications
4
145
0
1
Order By: Relevance
“…[1][2][3] There are two mechanisms proposed for those reactions, i.e., hydrogen atom transfer (HAT) and proton-coupled electron transfer (PCET) [4,5] reactions. In the HAT reaction, the hydrogen transfer occurs between the same sets of σ orbitals associated with breaking and forming bonds, which is typical of hydrocarbon combustion reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] There are two mechanisms proposed for those reactions, i.e., hydrogen atom transfer (HAT) and proton-coupled electron transfer (PCET) [4,5] reactions. In the HAT reaction, the hydrogen transfer occurs between the same sets of σ orbitals associated with breaking and forming bonds, which is typical of hydrocarbon combustion reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of a CI on a thermally activated reaction depends on the energetic accessibility of the dividing surface and of the seam of intersection. Examples of thermally activated reactions where the CI seam is (or can be) accessed under usual conditions involve chemiluminescence, energy transfer, reactions involving metal atoms (29,32), and hydrogen atom abstractions from phenolic antioxidants (69). The CIs in systems considered here are particularly interesting because of their relevance in nonreactive processes, such as attachment of metal atoms to aromatic systems, which is of utmost importance in organometallic chemistry and materials chemistry.…”
mentioning
confidence: 99%
“…In another study, leopoldini et al found that the addition of OH radical to caffeic acid is slightly favored with respect to the hydrogen atom transfer, while the single electron transfer is unlikely, since thermodynamically, it is unfavorable 9 . Mayer et al and Oksana et al reported that the reactivity of phenols toward free radicals, such as CH3 OO• and PhO, involved a PCET mechanism 10,11 . In this study, we describe the synthesis of quinozoline derivatives (Scheme 1) and we describe their characterization through spectral data (FT-IR, H-NMR) and elemental analysis (CHN) inadition to discuss the in vitro antioxidant activities of the compounds (3-6).…”
Section: Introductionmentioning
confidence: 99%